Neutrophil mediated postoperative photoimmunotherapy against melanoma skin cancer. Issue 35 (1st September 2021) - Wu, Yunyun; Han, Xiaoqing; Zheng, Runxiao; Cheng, Hongda; Yan, Jiao; Wu, Xiaqing; Hu, Yaqing; Li, Bing; Wang, Zhenxin; Li, Xi; Zhang, Haiyuan
Abstract : Neutrophils acted as carriers to deliver photoimmunotherapeutic nanoparticles for inhibiting the postoperative tumor recurrence. Abstract : Surgery is the primary treatment option for most melanoma; however, high tumor recurrence rate after surgical resection becomes the main cause of death in cancer patients. The development of efficient drug delivery nanosystems to inhibit postoperative tumor recurrence becomes very necessary. In the present study, IR780 molecules and TRP-2 peptide were encapsulated in the hydrophobic shell and hydrophilic interior of TAT peptide functionalized liposomes to form T LipIT NPs, which were further internalized into neutrophils (NEs) to achieve T LipIT/NEs. After being intravenously injected into postoperative B16F10-bearing mice, T LipIT/NEs could actively migrate toward the inflamed residual tumor and release T LipIT through neutrophil extracellular traps (NETs). Under NIR laser irradiation, the T LipIT exhibited both photothermal and photodynamic effects to induce immunogenic cell death for maturation of DCs, and simultaneously, to release TRP-2 peptide as a melanoma associated antigen to further strengthen the maturation of DCs, both of which prompts the activation of T cells and induces potent immune responses. T LipIT/NEs hold great potential for the inhibition of postoperative tumor recurrence.